2008
DOI: 10.1177/1545109708323130
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Recurrent Salmonella Meningitis in an Adult AIDS Patient in the United States

Abstract: The authors present a case of Salmonella sepsis and meningitis with a recurrence of the meningitis in a 36-year-old Hispanic, male AIDS patient. They discuss the mechanisms and routes in general and speculate on these items in this patient from the information available. Meningitis diagnosis and treatment in general and specifically in Salmonella cases are reviewed as well as the variations in AIDS patients. The probable reasons for the recurrence and etiology are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Our literature search found only 7 reported cases of Salmonella meningitis in adult patients in the United States with confirmed HIV infection [ 1 , 6 , 7 ]. Fraimow et al reported the first 3 cases of Salmonella meningitis in adults with HIV in the United States [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our literature search found only 7 reported cases of Salmonella meningitis in adult patients in the United States with confirmed HIV infection [ 1 , 6 , 7 ]. Fraimow et al reported the first 3 cases of Salmonella meningitis in adults with HIV in the United States [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 6 cases, 2 patients relapsed despite antibiotics and only 4 patients survived [ 1 ]. Vaughn et al reported an adult with HIV with recurrent Salmonella meningitis in the United States [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pueden ser leves y auto-limitadas o asociarse a un síndrome disentérico, con fi ebre, diarrea sanguinolenta, baja de peso y bacteriemia. Pueden tener, además, localizaciones extra-intestinales y manifestarse como fi ebre prolongada e incluso meningitis 68,69 . Tienen mal pronóstico si se asocian a intensa inmunosupresión con recuento de linfocitos T-CD4 inferior a 100 céls/mL y las recaídas son más frecuentes especialmente en la salmonelosis.…”
Section: Infecciones Bacterianas Entéricasunclassified
“…Patients present with common symptoms such as headache, fever, altered level of consciousness, and neck rigidity. A positive gram stain or culture of the cerebrospinal fluid (CSF) leads to its diagnosis [5]. Improper hygiene, unsanitary food, and unsatisfactory vaccination coverage in most areas of Pakistan have played a major role in the spread of the disease.…”
Section: Introductionmentioning
confidence: 99%